2022
DOI: 10.3390/jcm11113012
|View full text |Cite
|
Sign up to set email alerts
|

Primary Liver Transplantation vs. Transplant after Kasai Portoenterostomy for Infants with Biliary Atresia

Abstract: Introduction: Primary liver transplants (pLT) in patients with biliary atresia (BA) are infrequent, since most babies with BA undergo a prior Kasai portoenterostomy (KPE). This study compared transplant outcomes in children with BA with or without a prior KPE. We hypothesized that pLT have less morbidity and better outcomes compared to those done after a failed KPE. Methods: A retrospective review of patients with BA transplanted at our institution was performed. Patients were included if they received a pLT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Instead, a number of cohort studies comparing salvage LTx after bile drainage surgery with primary LTx found no significant difference in patient survival or graft survival but did find a significant increase in early postoperative morbidity, such as infection and reoperation 12,13 . Lemoine et al 7 reported waitlist mortality in patients with early failure after a portoenterostomy, and a recent study by Yoeli et al 14 analyzing 3438 patients with BA in a transplantation database in the United States, which included data on waitlist mortality, concluded that bile drainage surgery should be attempted first because it may enable LTx to be postponed beyond the first year of life, thereby improving survival without jeopardizing subsequent LTx outcomes. However, the latter study did not analyze postoperative morbidity and defined patients with LTx as those without a history of abdominal surgery albeit there were some issues in the study with possible miscategorization of the patients 14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, a number of cohort studies comparing salvage LTx after bile drainage surgery with primary LTx found no significant difference in patient survival or graft survival but did find a significant increase in early postoperative morbidity, such as infection and reoperation 12,13 . Lemoine et al 7 reported waitlist mortality in patients with early failure after a portoenterostomy, and a recent study by Yoeli et al 14 analyzing 3438 patients with BA in a transplantation database in the United States, which included data on waitlist mortality, concluded that bile drainage surgery should be attempted first because it may enable LTx to be postponed beyond the first year of life, thereby improving survival without jeopardizing subsequent LTx outcomes. However, the latter study did not analyze postoperative morbidity and defined patients with LTx as those without a history of abdominal surgery albeit there were some issues in the study with possible miscategorization of the patients 14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter study did not analyze postoperative morbidity and defined patients with LTx as those without a history of abdominal surgery albeit there were some issues in the study with possible miscategorization of the patients 14 . The previously cited monocentric study by Lemoine et al 7 noted that 5 of 14 patients with BA receiving primary LTx had previously received exploratory abdominal surgery. It is clear that certain patients with BA will not benefit from bile drainage surgery, and that primary LTx would benefit greatly if such patients could be accurately identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is heterogeneity in the reports of biliary complications; some studies reported no difference in the incidence of biliary complications between groups Two distinct populations can be seen in the patients who underwent prior Kasai group. However, most studies have not distinguished between these patients when performing analysis, which might have contributed to the heterogeneity of the outcomes reported across the studies [1][2][3][4][5][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Patients with K-EF tend to display similar characteristics to pLT at the time of transplantation, such as lower body weight and higher PELD score, in contrast to the K-LF group [1;5-7].…”
Section: Discussionmentioning
confidence: 99%